2004
DOI: 10.1103/physrevb.69.134417
|View full text |Cite
|
Sign up to set email alerts
|

Critical scattering of polarized neutrons in the invarFe65Ni35alloy

Abstract: The magnetic phase transition in the invar Fe 65 Ni 35 alloy has been investigated by small-angle polarizedneutron scattering ͑SAPNS͒ along with both three-dimensional neutron depolarization and thermal-expansion measurements. The data give evidence for a smeared phase transition. A spatial distribution in the Curie temperature T C is introduced to explain the experimental data. The local T C variations are described by the standard deviation of the transition temperature ⌬T C and by the characteristic length … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
8
0

Year Published

2005
2005
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 26 publications
1
8
0
Order By: Relevance
“…1 Nevertheless, some issues, especially those related with iron in a face centered cubic ͑fcc͒ lattice, the so-called ␥-Fe, are still a hot topic of discussion at the present. 2,3 Total-energy band calculations predict a very rich and complex magnetic phase diagram, 4,5 including the presence of large moment-volume instabilities, [6][7][8] responsible for the existence of Invar and anti-Invar behaviors. Contrary to the Invar effect, where a nearly zero thermal expansion is observed in some magnetically ordered materials, other systems exhibits, in the paramagnetic state, an anomalous thermal expansion larger than that described by a Grüneisen lattice.…”
Section: Introductionmentioning
confidence: 99%
“…1 Nevertheless, some issues, especially those related with iron in a face centered cubic ͑fcc͒ lattice, the so-called ␥-Fe, are still a hot topic of discussion at the present. 2,3 Total-energy band calculations predict a very rich and complex magnetic phase diagram, 4,5 including the presence of large moment-volume instabilities, [6][7][8] responsible for the existence of Invar and anti-Invar behaviors. Contrary to the Invar effect, where a nearly zero thermal expansion is observed in some magnetically ordered materials, other systems exhibits, in the paramagnetic state, an anomalous thermal expansion larger than that described by a Grüneisen lattice.…”
Section: Introductionmentioning
confidence: 99%
“…Grigoriev et al studied the magnetic phase transition in disordered Fe-Ni alloys doped with carbon. [4][5][6] The size of LOR depends on the doping concentration p in the following way R 0 ϳ͓p͑1− p͔͒ −1 . 22 However the present experimental data is not enough to test this prediction.…”
Section: Summary and Discussionmentioning
confidence: 99%
“…For example, LOR is needed to explain experiments in doped ferromagnets. [4][5][6] In addition the inhomogeneous phase has been extensively studied in various quantum phase transition in disordered systems. For example, it is found that there are two kinds of Mott transition: homogeneous and inhomogeneous.…”
Section: Summary and Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…7,18,19 Metastable fcc Fe-Cu phases are found to decompose into fcc Cu and bcc Fe phases at 1000 K. 19 Nevertheless, issues like Fe in Fe-Cu system exhibiting fcc structure, the so called c-Fe, is still a hot topic of discussion. 20,21 Negligible mutual solubility of both the constituent elements in equilibrium state also requires a detailed investigation of presence of small fraction of intermetallic compounds. Commercially, bcc Fe having nanosized Cu precipitates exhibits an enhanced thermal stability and an increased hardness.…”
Section: Introductionmentioning
confidence: 99%